Green Marketing in Community-Based Tourism: Strategies, Responses,Sustainability Outcomes, and Theoretical Foundations - Lady Faerrosa; Nanang Suryadi; Raditha Dwi Vata Hapsari (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
This article reviews empirical studies on green marketing in community-based tourism (CBT), as it is often treated merely as a promotional activity rather than an integral part of sustainable destination development. The study aims to identify the key determinants, major outcomes, and theoretical directions of green marketing in CBT. The method used is a systematic literature review with an empirical-only screening criterion. After excluding conceptual, review-based, and other non-empirical sources, 17 primary studies were retained. The findings show that green marketing in CBT is effective when supported by operational sustainability, active community participation, digital communication capability, and stakeholder collaboration. Strategies such as eco-labels, eco-branding, environmental advertising, community storytelling, social media communication, influencer promotion, visitor segmentation, and transparent destination branding are associated with stronger green trust, improved destination image, higher visit and purchase intention, repeat-visit intention, and more environmentally responsible tourist behavior. This article contributes by proposing an integrative framework linking community capability, green value propositions, communication channels, psychological mediators, and sustainability outcomes, while also highlighting the need for longitudinal impact measurement, stronger anti-greenwashing verification, comparative governance analysis, and greater theoretical consolidation.